(untitled) (International Seven Journal of Multidisciplinary, 2024)
Bearing in mind that Quality of Life at Work Management (QOLWM) can be defined as the “set of actions taken by an organization to implement managerial, technological and structural improvements and innovations in the work environment, and involves the following areas of knowledge: health, ecology, ergonomics, psychology, sociology, economics, administration and engineering” (Limongi-França, 1996). (Limongi-França, 1996), it could be assumed that in a school environment this practice would be more than natural, since it is an environment in which the main product is the improvement and development of its students.